Substrate-selective morphology of cesium iodide clusters on graphene - Vats, N; Wang, Y; Sen, S; Szilagyi, S; Ochner, H; Abb, S; Burghard, M; Sigle, W; Kern, K; van Aken, PA; Rauschenbach, S (American Chemical Society, 2020)
Formation and characterization of low-dimensional nanostructures is crucial for controlling the properties of two-dimensional (2D) materials such as graphene. Here, we study the structure of low-dimensional adsorbates of cesium iodide (CsI) on free-standing graphene using aberration-corrected transmission electron microscopy at atomic resolution. CsI is deposited onto graphene as charged clusters by electrospray ion-beam deposition. The interaction with the electron beam forms two-dimensional CsI crystals only on bilayer graphene, while CsI clusters consisting of 4, 6, 7, and 8 ions are exclusively observed on single-layer graphene. Chemical characterization by electron energy-loss spectroscopy imaging and precise structural measurements evidence the possible influence of charge transfer on the structure formation of the CsI clusters and layers, leading to different distances of the Cs and I to the graphene.